A Subset of Malignant Phyllodes Tumors Express p63 and p40: A Diagnostic Pitfall in Breast Core Needle Biopsies - Cimino-Mathews, Ashley (Am J Surg Pathol, 2014)
Breast phyllodes tumors are rare fibroepithelial neoplasms of variable grade, and one key differential of malignant phyllodes on core biopsy is sarcomatoid carcinoma. p63 is reported to be sensitive and specific for sarcomatoid carcinoma, with rare expression in phyllodes in limited series. The p63 deltaNp63 isoform, p40, is postulated to be more specific for squamous differentiation but has not previously been evaluated in breast phyllodes or sarcomatoid carcinoma. Tissue microarrays containing 34 unambiguous phyllodes tumors (10 benign, 10 borderline, 14 malignant), 13 sarcomatoid carcinomas, and 10 fibroadenomas were labeled by immunohistochemistry for p63, p40, CD34, and cytokeratins AE1/AE3, 34betaE12, and CK8/18. No borderline phyllodes tumor, benign phyllodes tumor, or fibroadenoma labeled with p63, p40, or cytokeratin. However, p63 labeled 57% malignant phyllodes tumors and 62% sarcomatoid carcinomas, and p40 labeled 29% malignant phyllodes (focal) and 46% sarcomatoid carcinomas. Among established markers, cytokeratins labeled 21% malignant phyllodes tumors (focal) and 100% sarcomatoid carcinomas. CD34 labeled 57% malignant phyllodes tumors and no sarcomatoid carcinomas. Focal p63, p40, and cytokeratin labeling can be seen in malignant phyllodes tumors but not in lowergrade fibroepithelial lesions, and immunoreactivity with these markers alone is not diagnostic of sarcomatoid carcinoma on core needle biopsy. In the differential diagnosis of malignant phyllodes, p40 is a more specific but less sensitive marker of sarcomatoid carcinoma than p63. These results are consistent with the sarcoma literature in which p63 labeling has been increasingly reported and suggest caution in classifying malignant spindle cell tumors of the breast on core biopsy.